2008
DOI: 10.1089/tea.2007.0261
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of Bone Marrow by Bone in Rat Femurs: The Bone Bioreactor

Abstract: During development and repair of bone, two distinct yet complementary mechanisms, intramembranous and endochondral, mediate new bone formation via osteoblasts. Because mechanical bone marrow ablation leads to the rapid and transient formation of new bone in the marrow cavity, we postulated that parathyroid hormone (PTH), which is a bone anabolic hormone, enhances the formation of new bone that forms after marrow ablation. We subjected the left femur of rats to mechanical marrow ablation, or sham operation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 26 publications
(32 reference statements)
2
19
1
Order By: Relevance
“…Mechanical BMX provokes a predictable sequence of events, including the formation of a blood clot with inflammation and capillary invasion, mesenchymal cell migration, osteoblast proliferation, and formation of new cancellous medullary bone, followed by osteoclastic bone resorption and bone marrow reconstitution . Previous studies have employed this model to investigate the effect of exogenous PTH on the formation of new bone that forms after marrow ablation . Those results showed that the abundance of bone formed in response to PTH1‐34 in the marrow cavity after marrow ablation is far more than that formed in response to either the hormone alone without marrow ablation, or to marrow ablation alone .…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical BMX provokes a predictable sequence of events, including the formation of a blood clot with inflammation and capillary invasion, mesenchymal cell migration, osteoblast proliferation, and formation of new cancellous medullary bone, followed by osteoclastic bone resorption and bone marrow reconstitution . Previous studies have employed this model to investigate the effect of exogenous PTH on the formation of new bone that forms after marrow ablation . Those results showed that the abundance of bone formed in response to PTH1‐34 in the marrow cavity after marrow ablation is far more than that formed in response to either the hormone alone without marrow ablation, or to marrow ablation alone .…”
Section: Introductionmentioning
confidence: 99%
“…New intramedullary bone was induced by femoral reaming as previously described in rats [28] and mice [29]. An incision was made on the right hind leg lateral to the knee and a 25G needle pushed through the cortex of the distal femur between the intercondyles and unilaterally up the medullary canal to loosen the marrow.…”
Section: Methodsmentioning
confidence: 99%
“…These data suggested that PTHrP is required for normal turnover of bone cells, and activation of apoptosis in mature osteoblasts could represent a potential mechanism whereby cells no longer forming matrix are cleared to provide access for new cells. Besides PTH’s clinical use for the treatment of osteoporosis, its potential for the application in fracture healing, tissue engineering and implant integration are being explored [6568]. …”
Section: Anabolic and Catabolic Actions Of Pth And Pthrp On Bonementioning
confidence: 99%